Polyphyly of Hylophilus and a new genus for the Tawny-crowned Greenlet (Aves: Passeriformes: Vireonidae) - Slager, David L.; Klicka, John (Zootaxa, 2014)
Once a catch-all taxon for various small, greenish passerines (Sclater 1881), today the genus Hylophilus Temminck contains 15 species of Neotropical greenlets in the avian family Vireonidae (Clements et al. 2013). Although Hylophilus species do share some common anatomical proportions and plumage features (Baird 1866; Ridgway 1904), some striking and concordant differences in habitat, voice, and iris color led Ridgely and Tudor (1989) to posit that the genus might contain sufficient diversity to warrant splitting into multiple genera.